A novel homozygous frameshift mutation in the DCC gene in a Pakistani family with autosomal recessive horizontal gaze palsy with progressive scoliosis‐2 with impaired intellectual development. Issue 2 (3rd November 2020) - Zaka, Ayesha; Shahzad, Shaheen; Rao, Hadi Zahid; Hashim, Yasmin; Basit, Sulman
Abstract: Horizontal Gaze Palsy with Progressive Scoliosis‐2 with Impaired Intellectual Development (HGPPS2) is a rare congenital disorder characterized by absence of conjugate horizontal eye movements, and progressive scoliosis developing in childhood and adolescence. We report three new patients with HGPPS2 in a consanguineous Pakistani family, presenting varying degrees of progressive scoliosis, developmental delays, horizontal gaze palsy, agenesis of corpus callosum, and absence of cerebral commissures. Analysis of genotyping data identified shared loss of heterozygosity (LOH) region on chromosomes 5p15.33‐15.31, 6q11.2‐12, and 18q21.1‐21.3 . A hypothesis‐free, unbiased exome data analysis detected an insertion of nucleotide A (c.2399dupA) in exon 16 of the DCC gene. The insertion is predicted to cause frameshift p.(Asn800Lysfs*11). Interestingly, DCC gene is present in the LOH region on chromosome 18. Variant (c.2399dupA) in the DCC gene is considered as the most probable candidate variant for HGPPS2 based on the presence of DCC in the LOH region, previously reported role of DCC in HGPPS2, perfect segregation of candidate variant with the disease, prediction of variant pathogenicity, and absence of variant in variation databases. Sanger Sequencing confirmed the presence of the novel homozygous mutation in all three patients; the parents were heterozygous carriers of the mutation, in accordance with an autosomal recessive inheritance pattern. DCC encodes a netrin‐1 receptor protein; its role in the development of the CNS has recently been established. Biallelic DCC mutations have previously been shown to cause HGPPS2. A novel homozygous variant in patients of the reported family extend the genotypic and phenotypic spectrum of HGPPS2.